Effect of postoperative rehabilitation on quality of life in patients with vulvar cancer - T. A. Blbulyan; A. G. Solopova; A. E. Ivanov; E. I. Kurkina (Акушерство, гинекология и репродукция)
Aim: to evaluate the quality of life parameters dynamics in patients with vulvar cancer I and II stages during postoperative rehabilitation.Materials and Methods. A prospective comparative randomized study included 47 women with vulvar cancer I–II stages, aged 38 to 70 years, with an average age of 56.3 ± 3.9 years. Patients were randomized into 2 groups: 24 of them underwent postoperative rehabilitation and 23 were included in the comparison group. Quality of life and sexual function, as well as psycho-emotional state were assessed using a set of questionnaires: quality of life of the European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30, Functional Assessment of Cancer Therapy-General (FACT-G) with an extension for vulvar cancer, Female Sexuality Index (FSFI) and WAM (well-being, activity, mood).Results. Patient who receiving postoperative rehabilitation even during the first three months, a reliable positive dynamics of all parameters of FSFI and EORTC, except cognitive function, was noted. At the same time, in the patients not undergoing postoperative rehabilitation program there was no reliable difference in the results of the questionnaires, except for FSFI, but the severity of changes was significantly less than in the patients of the research group. Dynamics in the EORTC parameters in women in postoperative rehabilitation averaged 14.8 points with 7.8 points in the comparison group. In the FACT-G questionnaire, the dynamics were even more pronounced with 19.9 and 6.8 points respectively. There was a reliable positive trend in improving the quality of sexual life and a decrease in the percentage of women suffer from pain and discomfort during sexual intercourse: from 25,0 % (n = 6) to 4,2 % (n = 1) in the study group and from 21,7 % (n = 5) to 13,0 % (n = 3) in the comparison group. Improvement in sexual desire and satisfaction during the year was noted in 5 (20.8 %) women in the study group and only 2 (8.7 %) in the comparison group.Conclusion. The developed program of postoperative rehabilitation of patients with vulvar cancer, which includes individual and group psychotherapy, "anti-cancer diet therapy", dosed physical activity, dynamic correction of vaginal biocoenosis showed high efficiency already during the first 6 months. All patients with vulvar cancer in the postoperative period should receive active rehabilitation aimed at correction of psycho-emotional state and sexual function, which will improve the quality of life and improve further prognosis.